Mitochondrial DNA polymorphism in seven cattle breeds in Malaysia - Yow, Weng Kit (2012)
Although the Kedah Kelantan (KK) is the indigenous cattle of Malaysia, a number of cattle breeds have been introduced into the country to enhance the local beef and dairy cattle industry. The cattle breeds in Malaysia comprise of Bos indicus types (present in tropical countries), Bos taurus types (indigenous to the European countries but is also found in Africa and Asia), and the hybrids of these two types of cattle. There are not many publications available on the origin of Asian cattle. There is a lack of studies on the molecular variation within and among the cattle breeds in Malaysia as well as the genetic relationship among these breeds. In addition, the phylogenetic relationship of cattle breeds in Asia, especially using mitochondrial DNA (mtDNA), has not been widely conducted. No study has been conducted on mtDNA polymorphism of Kedah Kelantan (KK), the indigenous cattle breed of Malaysia. Mitochondria are cytoplasmic organelle that contain DNA. MtDNA has many special features which has made it a popular marker to determine evolutionary and phylogenetic relationships. It has been used in studies to identify the genetic relationships between and within species of mammals. Displacement loop (D-loop) is the highly variable and most rapidly evolving region in the mtDNA. Variation observed in this region is frequently used for phylogenetic analysis of related breeds within species. The mtDNA cytochrome b (cyt b) is significantly conserved and, therefore, suitable for phylogenetic relationship and forensic investigations. It is suitable for between species comparison. Mitochondrial NADH dehydrogenase 5 (ND5) gene is another highly conserved genes and is commonly used for species identification. With the above in mind, this study was conducted to evaluate the mtDNA polymorphism in seven cattle breeds in Malaysia, namely KK, Brahman, Brakmas,Brangus, Charoke, Droughtmaster and Jersey at four regions of the mtDNA, which are the D-loop, cyt b and ND5 regions. Blood samples were randomly collected from 30 animals of each breed except for Brangus (n=17). DNA was extracted and quantified using a spectrophotometer. The D-loop, cyt b and two ND5 regions were amplified using specific primers. These regions were digested with nine, five and two restriction endonucleases (RE),respectively, generating 16 polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) loci. DNA cloning was performed on two samples of KK to obtain the nucleotide sequence for each of the four regions of mtDNA. The sequence information was compared with that for B. indicus and B. taurus which were available in the National Center for Biotechnology Information (NCBI) database. The total percentage of polymorphism for the loci was 50%. The ND5 locus recorded 100% polymorphism. Polymorphism at the D-loop locus was 44.44% and for the cyt b locus it was 40%. The DdeI, EcoNI and MboI RFLP patterns for D-loop, the MspI and MspR9I RFLP patterns for cyt b, and the HindIII and TasI RFLP patterns for ND5 loci were clearly able to distinguish between the B. indicus and B. taurus cattle breeds. Thus, these make them useful markers to detect variation between species. The dendogram generated using the PCR-RFLP mtDNA data showed two clusters for the seven cattle breeds. The KK, Brakmas, Charoke and Droughtmaster breeds were grouped together while the other cluster comprised of Brahman, Brangus and Jersey breeds. Alignment of the KK nucleotide sequences with those of B. indicus and B. taurus for the D-loop, cyt b and ND5/HindIII regions showed KK to be more similar to B. indicus than to B. taurus. However, comparison of the ND5/TasI region, showed KK to be similar to B. taurus instead of B. indicus. More regions of the mtDNA should be investigated and more RE should be used in order to determine the reliability of the result. Sequencing of more samples and from all breeds for the various regions would provide more information on the genetic structures and relationships among the cattle breeds.